Pemberdayaan Masyarakat di Masa Pandemi Covid-19 dalam Perspektif Human Security - Amelia Syauket, Amelia Syauket; Thamrin, Djuni (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
This article aims to find out various forms of community empowerment during the Covid-19 Pandemic in the perspective of human security. This article uses qualitative research methods with a phenomenological approach that is very appropriate to use to see one of the government’s functions in the form of Community Empowerment. By prioritizing library data sources, the discussion is presented in a descriptive-narrative manner. The conclusion that can be drawn from this research is that the function of government in the form of community empowerment, especially the provision of services in the health sector, has been going well by prioritizing the wider community with various program activities that directly touch the people affected by the COVID-19 pandemic. This is in line with the human security perspective that the State is here to protect the weak and helpless in the face of the COVID-19 pandemic.